APPLICATION OF ROAD MINIMUM SERVICE STANDARD IN WEST JAVA - HERMAWAN (NIM. 250 02 037), EBBY
Act of the Republic of Indonesia number 38/2004 about road states that road management should fulfil a minimum service standard, whereas the minimum service standard is defined by the decree of Minister of Settlement and Regional Infrastructure number 534/KPTSIM/2001. At the end of the year of 2004, the performance of the provincial road and non status road of West Java, based on indicator of stability, shows that 255.13 km (12,84%) provincial roads and 136.52 km (35,84%) non status roads in length under unstable condition. This indicates that according to road condition aspect, there are several roads under the Minimum Service Standard, accessibility aspect and mobility aspect. This study shows that the achievement of Minimum Service Standard of the road network in West Java for accessibility index is 0.77 under the Minimum Service Standard, for mobility index is 0.58 has achieved the Minimum Service Standard value, and for accident index of 0,104. Whereas the achievement of the Minimum Service Standard on the road surface roughness condition shows that 247.702 km (12,47%) length of provincial roads and 135.65 km (35,61%) length of non status roads under the Minimum Service Standard condition. On the road width requirement 625.75 km (31,50%) length of provincial roads and 110.382 km (28,98%) length of non status roads under the Minimum Service Standard condition. For entire provincial road of West Java, to achieve the Minimum Service Standard, treatment to 879.294 km length of the road is needed with a budget of as much as Rp. 962,302,454,000.00 and divided to pavement management group of 143,102 km length of the road is needed on as much as Rp. 123,181,310,000.00 budget, pavement and widening management group of 240,250 km length of the road is needed with budget of as much as Rp. 378,350,810,000.00, and widening management group of 495,882 km length of the road is needed Rp. 460,770,334,000.00 budget. Due to budget constraint, a prioritization program on road management has to be taken to meet the Minimum Service Standard needs. The multi criteria analysis is used as prioritizing tool, and the criteria are: (1) Road link accessibility function, (2) Road link condition, and (3) Road link Serviceability. Criteria weighing result based on the perception of respondent of stake holders, the government of West Java and the society, shows weighing results of; (1) 0.510 for road link accessibility function criteria, (2) 0.268 for Road link condition criteria, and (3) 0.222 for Road link Serviceability criteria. Prioritization of road management for each group was carried out by comparing the performance matrix of every road link. The performance matrix is a multiplication of criteria weight and scoring result. Prioritization result shows that for the three management groups, the non status roads have the highest priority are as follow : (a) for pavement management group, rank 1 is road link of Tegalbuleud - Agrabinta = 36,100 km in length and 9,718 for performance value, (b) for pavement and widening management group, rank 1 is road link of Surade - Tegalbuleud = 37,700 km in length and 9,173 for performance value, (c) for widening management group, rank 1 is road link of Cipatujah - Kalapagenep = 41,35 km in length and 8,366 for performance value.